Dual-Layer Flexible Capacitance Sensor with Wide Range and High Sensitivity - Benyuan Fu; Zipei Wang; Kun Chen; Zebing Mao; Hao Wang; Benxiang Ju; Yanhong Peng (Actuators)
Flexible pressure sensors have attracted great attention due to their extensive applications in human–computer interaction and health monitoring. So far, the development of flexible pressure sensors that balance high sensitivity and a wide measurement range remains a challenge. Herein, a double-layer dielectric structure with a surface convex structure is reported for the preparation of flexible capacitive pressure sensors. The double-layer dielectric structure, which is composed of a silicone rubber-based conductive elastomer with a surface micro-convex structure and a PVA-H-based conductive elastomer, balances the advantages and disadvantages of the two conductive elastomer dielectrics. It can form a complete micro-capacitive network under relatively large pressures, enabling the sensor to have high sensitivity at different stages (1.7 kPa−1, 0–104 kPa; 19.14 kPa−1, 104–140 kPa), thus achieving a dual enhancement of sensitivity and sensing range. Additionally, the sensor has been successfully applied to scenarios such as monitoring of human breathing, speaking, and movement, as well as mouse clicks, demonstrating its great potential in the fields of health monitoring and human–computer interaction applications.